DAMPAK KINERJA INTERNAL DAN KONDISI MAKRO EKONOMI TERHADAP PROFITABILITAS PADA PERBANKAN - Bayu Widokartiko; Noer Azam Achsani; Irfan Syauqi Beik (Jurnal Aplikasi Bisnis dan Manajemen (JABM), 2016)
The objectives of this study are 1) to analyze and measure the impacts of internal performance variables of the conventional and Islamic banking toward profitability; 2) to analyze and measure the impacts of macro-economic variables influencing the profitability of conventional and Islamic banking. This research used Granger causality and Vector Auto Regressive (VAR)/Vector Error Correction Model (VECM) as the data analysis tools. The results of this study confirm that Islamic banking has a more stable profitability in response to macroeconomic conditions as compared to the conventional banking system. The response of the profitability toward the influence of the movement of macroeconomic variables can conclude that the Islamic banking can be stable more quickly in CURRENCY and INFLATION. The influence of the performance variable of the internal banking toward macroeconomic occurs more frequently in conventional banks. CAR internal performance variable is influential on BI Rate, and LDR is influential on currencies. Key words: profitability, Islamic banking, granger causality, VAR, VECM